Activation of NLRP3 inflammasome in human middle ear cholesteatoma and chronic otitis media. (1st February 2016) - Kariya, Shin; Okano, Mitsuhiro; Zhao, Pengfei; Kataoka, Yuko; Yoshinobu, Junko; Maeda, Yukihide; Ishihara, Hisashi; Higaki, Takaya; Nishizaki, Kazunori
Abstract: Conclusions : The nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome plays an important role in the pathogenesis of middle ear diseases. Modulation of inflammasome-mediated inflammation may be a novel therapeutic strategy for cholesteatoma and chronic otitis media. Objective : NLRP3 inflammasome is a critical molecule mediating interleukin (IL)-1 β responses. However, the expression of NLRP3 in the pathogenesis of cholesteatoma and chronic otitis media has not been fully examined. This study sought to assess the expression of NLRP3, ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain and a pyrin domain), and caspase-1 in middle ear tissues in patients with cholesteatoma or chronic otitis media. Methods : Middle ear tissue samples were obtained from patients with cholesteatoma or chronic otitis media. Control middle ear samples were collected during cochlear implant surgery of patients without middle ear inflammation. The expression of NLRP3, ASC, and caspase-1 were examined by reverse transcription polymerase chain reaction (RT-PCR) assay and immunohistochemical study. Results : The levels of mRNA of NLRP3, ASC, and caspase-1 were significantly elevated in cholesteatoma and chronic otitis media as compared with that of normal controls. The proteins of NLRP3, ASC, and caspase-1 were observed in infiltrating inflammatory cells in cholesteatoma and chronic otitis media.